XML for data architects : designing for reuse and integration - Bean, James (James D.) (Morgan Kaufmann Series in Data Management Systems Ser., 2003)
"The book addresses a sorely missing set of considerations in the real world ... This is a very timely book."--Peter Herzum, author of Business Component Factory and CEO of Herzum SoftwareXML is a tremendous enabler for platform agnostic data and metadata exchanges. However, there are no clear processes and techniques specifically focused on the engineering of XML structures to support reuse and integration simplicity, which are of particular importance in the age of application integration and Web services. This book describes the challenges of using XML in a manner that promotes simplification